2018
DOI: 10.1021/jacs.8b08739
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Takai Olefination Reagent via Tris(tert-butoxy)siloxy Variants

Abstract: The elusive Takai olefination reagent, namely, the iodo-methylidene Cr(III) complex [CrCl(CHI)(thf)], has been isolated by careful handling of the reaction between CrCl and CHI in THF at -35 °C. Alternatively, treatment of [Cr(OSi(O tBu))] with CHI gave the mixed-valent dihalido-methanide complex [CrI(OSi(O tBu))(CHI)], featuring a Cr(III)-CHI moiety. In the presence of TMEDA nucleophilic attack at CHI occurred generating the zwitterionic species [Cr(OSi(O tBu))(tmeda-CHI)][I]. Complexes [CrCl(CHI)(thf)] and [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 55 publications
0
17
0
3
Order By: Relevance
“…The Cr–O distances in 3 are 1.9360(10) and 1.9345(10) Å matching those in Cr[OSi(O t Bu) 3 ] 2 (tmeda) with 1.9307(12) and 1.9380(12) Å. 10 Monomeric chromous siloxides are rare and additionally feature trans -square-planar Cr[OSi(O t Bu) 3 ] 2 (NHEt 2 ) 2 , 8 and Cr(OSi t Bu 3 ) 2 (OCPh 2 ) 2 . 6…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…The Cr–O distances in 3 are 1.9360(10) and 1.9345(10) Å matching those in Cr[OSi(O t Bu) 3 ] 2 (tmeda) with 1.9307(12) and 1.9380(12) Å. 10 Monomeric chromous siloxides are rare and additionally feature trans -square-planar Cr[OSi(O t Bu) 3 ] 2 (NHEt 2 ) 2 , 8 and Cr(OSi t Bu 3 ) 2 (OCPh 2 ) 2 . 6…”
Section: Resultsmentioning
confidence: 61%
“…The dihedral distortion between the planes O1–Cr1–O2 and N1–Cr1–N2 was determined as 26.15° in stark contrast to 8.03° (calculated with MERCURY) 24 for Cr[OSi(O t Bu) 3 ] 2 (tmeda). 10 These differences likely originate from the distinct sterics of i Pr versus O t Bu. The Cr–O distances in 3 are 1.9360(10) and 1.9345(10) Å matching those in Cr[OSi(O t Bu) 3 ] 2 (tmeda) with 1.9307(12) and 1.9380(12) Å.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Die aktive Spezies wird häufig in situ über die Dehalogenierungsroute gebildet, wobei CrCl 2 und CHX 3 (X = Cl, Br, I) als Hauptkomponenten in variablen Verhältnissen zum Einsatz kommen. [17] Vor kurzem ist es uns gelungen die Festkçrperstruktur des Halogenalkyliden-Komplexes B [18] zu bestimmen und damit die ursprünglich von Takai vorgeschlagene Verbindung zu bestätigen. Bei [19] Die Cr-(m 3 -CH)-Abstände in 1 betragen 2.018(3)/2.019(3)/ 2.022(3) und sind damit im Vergleich zu Theopolds Methylidin [Cp 3 Cr 3 (m 2 -Cl) 3 (m 3 -CH)] (A; 1.935(10) und 1.949-( 14) ) wie auch die Cr-Cl-Abstände (2.3328(7) bis 2.4186-( 7) ) versus 2.348(4) bis 2.360(4) ) leicht verlängert.…”
Section: Introductionunclassified
“…8 f –8 i Takai et al reported that chromium-catalyzed cyclopropanation of alkenes with Me 3 SiCHI 2 proceeds in the presence of catalytic amounts of chromium complex and excess Mn powder as a reducing reagent, from which gem -dichromiomethane complexes ( Cr2–SiMe3 ) are isolated ( Fig. 1b ), 9 a and, similarly, Anwander et al isolated an iodomethyl-bridged dichromium complex by treating CrCl 2 with CHI 3 as a key intermediate species for cyclopropanation to give iodocyclopropanes. 9 b…”
Section: Introductionmentioning
confidence: 99%